TiO2 Nanotubes Promote Osteogenic Differentiation Through Regulation of Yap and Piezo1 - Kong, Keyu; Chang, Yongyun; Hu, Yi; Qiao, Hua; Zhao, Chen; Rong, Kewei; Zhang, Pu; Zhang, Jingwei; Zhai, Zanjing; Li, Huiwu (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Surface modification of titanium has been a hot topic to promote bone integration between implant and bone tissue. Titanium dioxide nanotubes fabricated by anodic oxidation has been a mature scheme and reported to promote osteogenesis in vitro. However, mechanisms behind such phenomenon remain elusive. In this study, we verified enhanced osteogenesis of BMSCs on nano-topography titanium in vitro and proved its effect in vivo by constructing a bone defect model in rats. What is more, the role of mechanosensitive molecule Yap is studied in this research by application of Yap inhibitor verteporfin and knockdown/overexpression of Yap in MC3T3-E1 cells. Piezo1 is a mechanosensitive ion channel discovered in recent years and found to be elemental in bone metabolism. In our study, we preliminarily figured out the regulatory relationship between Yap and Piezo1 and proved Piezo1 as a downstream effector of Yap and nanotube-stimulated osteogenesis. In conclusion, this research proved that nano topography promoted osteogenesis by increasing nuclear localization of Yap and activating the expression of Piezo1 downstream.